Influence of Combustion Characteristics and Fuel Composition on Exhaust PAHs in a Compression Ignition Engine - Hamisu Adamu Dandajeh; Midhat Talibi; Nicos Ladommatos; Paul Hellier (Energies, 2019)
This paper reports an experimental investigation into the effects of fuel composition on the exhaust emission of toxic polycyclic aromatic hydrocarbons (PAHs) from a diesel engine, operated at both constant fuel injection and constant fuel ignition modes. The paper quantifies the US EPA (United State Environmental Protection Agency) 16 priority PAHs produced from combustion of fossil diesel fuel and several model fuel blends of n-heptane, toluene and methyl decanoate in a single-cylinder diesel research engine based on a commercial light duty automotive engine. It was found that the level of total PAHs emitted by the various fuel blends decreased with increasing fuel ignition delay and premixed burn fraction, however, where the ignition delay of a fuel blend was decreased with use of an ignition improving additive the level of particulate phase PAH also decreased. Increasing the level of toluene present in the fuel blends decreased levels of low toxicity of two to four ring PAH, while displacing n-heptane with methyl decanoate increased particulate phase adsorbed PAH. Overall, the composition of the fuels investigated was found to have more influence on the concentration of exhaust PAHs formed than that of combustion characteristics, including ignition delay, peak heat release rate and the extent of the premixed burn fractions.